Purification and characterization of the inducible a agglutinin of Saccharomyces cerevisiae. - Watzele, M (1988)
A cell surface glycoprotein induced by the mating pheromone alpha factor in Saccharomyces cerevisiae a cells has been purified to homogeneity. At 4 x 10(-9) M it strongly inhibits mating-type-specific agglutination between a and alpha cells. The protein is solely O-glycosylated. It consists of 29% carbohydrate and its apparent molecular mass is 22 kd on SDS gels. After HF treatment it behaves like a protein of 13 kd; therefore its true molecular mass probably is close to 18 kd. Mild periodate treatment destroys the biological activity of the purified protein. The protein contains one cysteine, no arginine, and 27% of the amino acids are serine and threonine residues, two thirds of which are glycosylated. With a polyclonal antibody the glycoprotein can already be detected at the cell surface 15 min after pheromone addition. The inducible antigen is not expressed in a specific phase of the cell cycle; it first appears exclusively on the growing bud. Mother cells express the antigen on their surface only after the daughter cells have separated; it is then localized at the tip of the pear-shaped 'shmoo'. Using the secretory ts-mutant sec 18 is shown that a mannosylated precursor of a agglutinin accumulates at the endoplasmic reticulum.